2004
DOI: 10.4314/eamj.v81i7.9187
|View full text |Cite
|
Sign up to set email alerts
|

Hysteroscopic surgery at the Aga Khan Hospital, Nairobi

Abstract: Objectives: To determine the experience, acceptability and outcome of hysteroscopic surgery at the Aga Khan Hospital, Nairobi. Design: A retrospective study. Setting: Aga Khan Hospital, Nairobi. Patients: Between May 2000 and April, 2003, 463 cases of hysteroscopy were undertaken at the Aga Khan Hospital, Nairobi, of these 54 patients (11.7%) underwent various hysteroscopic surgical procedures. A review of these cases and their outcomes are analysed and presented. Results: In a thirty six month period 463 case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…This compares favorably with the 0.7% reported in Kenya 6 and 0.28% by Jansen et al 3 The patient in our study was a 33 years old para 1 +1 lady who had general anesthesia for combined hysteroscopy and laparoscopy. She developed apnea after the procedure for which she needed mouth to mouth resuscitation, cardiac massage and oxygen by face mask.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This compares favorably with the 0.7% reported in Kenya 6 and 0.28% by Jansen et al 3 The patient in our study was a 33 years old para 1 +1 lady who had general anesthesia for combined hysteroscopy and laparoscopy. She developed apnea after the procedure for which she needed mouth to mouth resuscitation, cardiac massage and oxygen by face mask.…”
Section: Discussionsupporting
confidence: 88%
“…This was much higher than the 16.6% reported at the Aga Khan hospital in Kenya. 6 Majority of our patients (71.1%) had previously terminated one or more pregnancies and these are usually unsafe abortions, as abortion is still illegal in Nigeria. The result could be an increase in uterotubal infections and hence adhesions.…”
Section: Discussionmentioning
confidence: 94%
“…In Kenya, Parkar et al reported the first cases of LAVH (11). The outcomes of 149 cases of locally performed LAVH were analysed, in this paper.…”
Section: Resultsmentioning
confidence: 99%
“…In Kenya, hysteroscopic surgery at a major regional hospital increased from 50 in year 2000 to 159 cases two years later. All surgeries were performed by senior faculty (consultants) and did not include doctors in training [21].…”
Section: Hysteroscopymentioning
confidence: 99%